Effect of plant and microalgae on immune-related genes and resistance of nile tilapia (Oreochromis niloticus) against Aeromonas hydrophila - Tasneem Ahmed Abdelmohsen; Adel Hassan Saad; Rasha A. Al wakeel; Sabreen E. Fadl; Awatef Hamed Hamouda (Scientific Reports)
Abstract Nile tilapia, is a crucial fish for warmwater aquaculture globally and plays a key role in food security. The experiment’s goal was to ascertain the actual effects of lemongrass and/or Arthrospira platensis (A. platensis) on Oreochromis niloticus (O. niloticus) growth. Along with liver and kidney functioning, some organ histopathology, and the expression of genes linked to immunity in liver tissue both before and after an infection with Aeromonas hydrophila (A. hydrophila). There were four diets created: with the first serving as a control group and being additive-free, while the second included 7.5 g kg− 1 of diet of A. platensis, the third included 200 mg kg− 1 of diet of lemongrass (Cymbopogon citratus), and the fourth group included lemongrass and A. platensis. The results of the growth trail were significantly higher in the treatment groups, especially with A. platensis treatment. However, the results of the biochemistry and immunological assay were pronounced with improved intestinal morphometry in the combination groups without pathological lesions. Moreover, the antioxidant and proinflammatory cytokine gene expressions improved with the treatments used. After experimental challenges, the results of the treatment groups showed the immunomodulatory effects of A. platensis and lemongrass oil against A. hydrophila infection. Thus, A. platensis alone or with lemongrass improved growth performance before experimental infection. After experimental infection, they decreased mortality rate and pathological lesions in liver and spleen and improved biochemical parameters and antioxidant and proinflammatory cytokine gene expression.